Gastric Perforation Following Dog Bite in a Child - Singh, Shailendra Pal; Verma, Shashank; Singh, Praveen; Pandey, Anand (Journal of Child Science, 2018)
Dog bite in children leading to visceral injury is a very uncommon clinical scenario. We treated a 6-year-old child who had a history of dog bite over the abdomen. At laparotomy, one perforation was found on the anterior surface of the stomach. The perforations were repaired primarily. The child made an uneventful postoperative recovery.
Keywords: gastric perforation; dog bite; pediatric gastric perforation